Women’s Economic Participation and the Impact of Regulatory Barriers - Adnane, Souad (World Bank, Washington, DC, 2021)
Many countries seek to improve women’s economic participation with the introduction of targeted laws and regulations. The impact of these reforms appears significant, although the supporting evidence is stronger in some areas than others. This insight paper considers the impact of legal discrimination and the absence of protective legislation on women’s economic outcomes, namely employment and earnings. It also explores the various pathways or channels through which laws and regulations affect those outcomes. An understanding of those mechanisms is important to the effective design and implementation of gender equal and gender sensitive laws and policies. A survey of the literature uncovered five key pathways that individually and in combination can help structure and improve the understanding of how legal reform impacts women’s employment and earnings. The available literature offered more causal evidence in some reform areas, namely property rights, retirement, and divorce laws, than in others. Empirical evidence from the remaining areas (childcare leave policies, occupational segregation, legal capacity within marriage) still establishes significant and strong associations, especially in the first area, between the studied legal reforms and women’s economic outcomes. Findings reported in the area of legal protections from violence and discrimination remain limited and inconclusive. There is a significant gap in the literature in terms of studies covering certain reforms in developing countries which undermines the generalizability of the findings. The paper concludes that although legal reform is not enough to bring about change, it is a critical first step in initiating social change and promoting women’s economic participation and women’s employment in the formal sector.